Temporobasal, Transsphenoidal Meningoencephalocele Becoming Symptomatic with Spontaneous Cerebrospinal Fluid Rhinorrhea: Diagnostic Work-up and Microsurgical Strategy - Keric, Naureen; Burger, Ralf; Elolf, Erck; Wrede, Arne; Rohde, Veit (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background We report the rare case of an adult transsphenoidal meningoencephalocele and outline the microneurosurgical strategy. Clinical history, the findings of computerized tomography (CT) scans and magnetic resonance imaging (MRI), the microsurgical procedure, and histopathology are reported.Case Report A 54-year-old female patient complained about cerebrospinal fluid (CSF) rhinorrhea; a transnasal biopsy of a mass in the maxillar sinus prior to diagnostic work-up was performed elsewhere. Persisting CSF leakage prompted CT and MRI, which showed brain tissue extending from the left middle cranial fossa into the left sphenoid sinus through several bony defects. The diagnosis of a transsphenoidal meningoencephalocele was made, and the lesion was targeted via a subtemporal intradural approach with resection of the herniated brain tissue and closure of the bony as well as of dural defects. The postoperative course was uneventful without recurrence of the CSF fistula.Conclusion The transsphenoidal subtype of basal meningoencephaloceles is exceedingly rare. Nonetheless, it has to be considered as a differential diagnosis if a nasal or intrasphenoidal mass is diagnosed. Otherwise, unjustified biopsy or unsuccessful management of CSF leakage could not be avoided. The intradural subtemporal approach is effective to treat the transsphenoidal type of basal meningoencephaloceles.
Keywords: temporobasal; transsphenoidal meningoencephalocele; rhinorrhea; skull base surgery